Writing Process Differences in Subgroups Reflected in Keystroke Logs. (October 2019) - Guo, Hongwen; Zhang, Mo; Deane, Paul; Bennett, Randy E.
We used an unobtrusive approach, keystroke logging, to examine students' cognitive states during essay writing. Based on data contained in the logs, we classified writing process data into three states: text production, long pause, and editing. We used semi-Markov processes to model the sequences of writing states and compared the state transition time and probability for demographic subgroups that were matched on writing proficiency. Results suggested that the subgroups employed different processes in essay writing.